Dóra Maurer - Bingham, Juliet (Tate Publishing, 2019)
Published to accompany a remarkable 2019 display at Tate Modern, this book will examine the full career of Hungarian artist Dora Maurer (b.1937), spanning over four decades of her experimental practice from the 1970s to the present. From her early graphic works, photographs and films, to her 'displacement' canvases and most recent large-scale paintings which explore how geometric forms are affected by colour and colour perception, this publication will reveal Maurer's persistent experimentation with production processes and her innovative take on traditional techniques. The show will introduce aspects of Maurer's early practice including graphic works, serial photographic works and structural films from the 1970s and 1980s. Maurer trained in graphic techniques, and in her graphic works she often examines the movement of markings left by different materials and production processes. Her works, be they photographs, graphic work or films, share a preoccupation with structure, relativity of perception and exploration of the medium's limits. Essay include an introductory overview by Tate curator Juliet Bingham; Klara Kemp-Welch examines Maurer's early works and pedagogical activities between 1975-7; Carly Whitefield writes on the artist's film works and the state-run Balazs Bela Studio; and David Feher surveys Maurer's practice from the 1980s to the present day
Catalogue of an exhibition held at Tate Modern, London, UK, 5 August 2019 to 5 July 2020
Keywords: Maurer, Dóra -- 1937-; Maurer, Dóra / 1937- / Exhibitions; Art, Hungarian / 20th century / Exhibitions; Maurer, Dóra / 1937-; Exhibition catalogs; Ausstellungskatalog -- Tate Modern -- 05.08.2019-05.07.2019 -- London; Bildband